2014
DOI: 10.1182/blood-2014-01-550319
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach to hemostasis: 3. Thrombus consolidation regulates intrathrombus solute transport and local thrombin activity

Abstract: Hemostatic thrombi formed after a penetrating injury have a distinctive structure in which a core of highly activated, closely packed platelets is covered by a shell of less-activated, loosely packed platelets. We have shown that differences in intrathrombus molecular transport emerge in parallel with regional differences in platelet packing density and predicted that these differences affect thrombus growth and stability. Here we test that prediction in a mouse vascular injury model. The studies use a novel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
184
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(198 citation statements)
references
References 23 publications
12
184
0
2
Order By: Relevance
“…Thrombi perfused with whole blood containing heparin lysed significantly faster than whole blood alone, highlighting the importance of on-going fibrin formation in these thrombi as a result of procoagulant activity. Notable work by Stalker et al 66 has recently shown that integrin a IIb b 3 outside-in signaling localizes thrombin activity within the core region of thrombi by minimizing solute transport. Our studies on plasminogen localization and plasmin activity suggest that it may be regulated by similar mechanisms via the interaction of fibrin(ogen) with a IIb b 3 within the microenvironment of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombi perfused with whole blood containing heparin lysed significantly faster than whole blood alone, highlighting the importance of on-going fibrin formation in these thrombi as a result of procoagulant activity. Notable work by Stalker et al 66 has recently shown that integrin a IIb b 3 outside-in signaling localizes thrombin activity within the core region of thrombi by minimizing solute transport. Our studies on plasminogen localization and plasmin activity suggest that it may be regulated by similar mechanisms via the interaction of fibrin(ogen) with a IIb b 3 within the microenvironment of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin activity in this model extends as a gradient from the site of vascular injury [73][74][75][76] and is necessary for full platelet activation and a granule secretion. 51,77 Our results indicate that ADP signaling reinforces platelet activation at the edge of this gradient where thrombin activity starts to decline.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linking results in the stabilization of the viscoelastic fibrin network, which has many fibers originating from platelet aggregates (6)(7)(8)(9). The activated platelets are able to generate contractile forces that are propagated through the cross-linked fibrin fibers (10,11), effectively resulting in a reduction of the clot volume (12,13). The volume reduction of the clot, or clot contraction, has been suggested to play a critical role in hemostasis (14), wound healing, and the restoration of blood flow past otherwise obstructive blood clots (15).…”
Section: Introductionmentioning
confidence: 99%